Symbolism and Irony in I Got Flowers Today: Tragic Domestic Love Cycle - Riska Atni Dwi Putri; Endang Yuliani Rahayu (Journal of Law, Politic and Humanities, 2026)
This study attempts to analyze Paulette Kelly’s poem I Got Flowers Today focusing on the tragic cycle of love and domestic violence as revealed through symbolism and irony. Domestic violence in the poem is portrayed as a continuous cycle involving verbal abuse, physical violence, emotional manipulation, economic dependence, and psychological fear rather than a sudden act. This study examines three main questions: the causes of domestic violence in Paulette Kelly’s I Got Flowers Today, the use of symbolism and irony to portray abusive relationship patterns, and the effects of violence on the victim. The research applies a qualitative descriptive approach through text-based analysis. The primary data source is the poem I Got Flowers Today, while secondary data are obtained from books, journal articles, and theories related to New Criticism, symbolism, irony, and domestic violence. The analysis is conducted through close reading by applying Cleanth Brooks’ theory of symbolism and irony, supported by Laurence Perrine’s concept of poetry. The findings reveal that flowers function as a central symbol representing false love, emotional manipulation, and ultimately death, while irony appears through the contrast between romantic gestures and acts of violence. The poem also depicts the severe emotional, psychological, physical, and social effects of domestic violence on the victim, which ultimately lead to the loss of freedom and life. This study concludes that I Got Flowers Today is not only a literary work but also a powerful social criticism that raises awareness of domestic violence and challenges the romanticization of abuse in society.